Respiratory Disease in the COVID-19 Era - Okamoto, Masaki (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Coronavirus disease 2019 (COVID-19) is a new respiratory disease caused by infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) that caused a global pandemic. COVID-19 patients often develop acute respiratory distress syndrome (ARDS), which involves acute and lethal respiratory failure. In a meta-analysis, the median incidence of ARDS in COVID-19 patients was found to be 35 (2-79)%, while the mortality rate in COVID-19-associated ARDS patients was found to be 39 (12.5-73.1)% (Hasan, et al. Expert Rev Repoir Med. 2020; 14: 1149). As of 12 December 2021, 270,373,764 cases had been confirmed as COVID-19 and 5,321,321 cases had resulted in death, according to the World Health Organization webpage. Various symptoms such as persistent fatigue, myalgia, and insomnia can persist after recovery from COVID-19; these symptoms are called "long COVID-19". Patients with COVID-19 who survive but develop pulmonary fibrosis may experience persistent dyspnea upon exertion, a decrease in pulmonary function, and/or a radiological abnormal shadow. Antifibrotic drugs including nintedanib and pirfenidone are candidate drugs for the treatment of pulmonary fibrosis due to COVID-19; randomized controlled trials are ongoing. However, there are limited studies about respiratory disease caused by COVID-19. Given the clinical significance of this topic and its impact on clinical practice and public health, Medicina have published a Special Issue entitled "Respiratory Disease in the COVID-19 Era" with the aim of gathering accurate and up-to-date scientific information of this topic.